2021
DOI: 10.3390/ani11102880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender on Meat Quality from Adult Obsolescent Horses

Abstract: The objective of the study was to assess the influence of gender, age, and carcass weight on the properties of meat from adult horses slaughtered in Lithuania. M. pectoralis profundus of twenty-six obsolescent horses from 3 to 21 years of age were used in the experiment. Gender appeared to affect the horse meat properties. Stallions demonstrated (p < 0.01 and p < 0.05, respectively) lower content of dry matter and also considerably lower (p < 0.001 and p < 0.01) intramuscular fat content compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(98 reference statements)
1
6
2
Order By: Relevance
“…Fatty acid identification was performed by comparing the retention times with those of known fatty acids, and the results were expressed as mg/100 g of fat. Atherogenic index (AI) and thrombogenic index (TI) were calculated using the following equations, in order to evaluate the atherogenic activity of C12:0, C14:0, and C16:0 and the thrombogenic activity of C14:0, C16:0, and C18:0 [ 24 ]: AI: C12:0 + (4 × C14:0) + C16:0 (MUFA + PUFA) TI: (C14:0 + C16:0 + C18:0) (0.5 × MUFA) + O.5 × PUFA n − 6 + 3 × PUFA n − 3 + (n − 3/n − 6) …”
Section: Methodsmentioning
confidence: 99%
“…Fatty acid identification was performed by comparing the retention times with those of known fatty acids, and the results were expressed as mg/100 g of fat. Atherogenic index (AI) and thrombogenic index (TI) were calculated using the following equations, in order to evaluate the atherogenic activity of C12:0, C14:0, and C16:0 and the thrombogenic activity of C14:0, C16:0, and C18:0 [ 24 ]: AI: C12:0 + (4 × C14:0) + C16:0 (MUFA + PUFA) TI: (C14:0 + C16:0 + C18:0) (0.5 × MUFA) + O.5 × PUFA n − 6 + 3 × PUFA n − 3 + (n − 3/n − 6) …”
Section: Methodsmentioning
confidence: 99%
“…Fatty acid identification was performed by comparing the antioxidant standard butylated hydroxytoluene (BHT) with gas chromatographic retention times. Atherogenic index (AI) and thrombogenic index (TI) were calculated using the equations: AI: (C12:0 + 4 × C14:0 + C16:0)/Mono Unsaturated Fatty Acids (MUFA) + Poly Unsaturated Fatty Acids (PUFA n-6 + PUFA n-3) TI: (C14:0 + C16:0 + C18:0)/(0.5 × MUFA) + (0.5 × PUFA n-6) + (3 × PUFA n-3) + (PUFA n-3/PUFA n-6) to provide specific lipid quality parameters, indicating that C12:0, C14:0, and C16:0 are atherogenic and that C14:0, C16:0, and C18:0 are thrombogenic [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some other authors have reported AI indexes [ 44 , 56 ] and similar [ 54 ] or higher TI indexes [ 42 ], but a lower h/H ratio [ 54 ]. Compared to pork [ 61 ], all lipid quality indices such as AI, TI indexes and h/H ratio of goose meat are more favourable for consumer health, however, if compared to horse meat [ 62 ], goose meat exhibits more favourable AI and h/H ratio. The peroxidizability index (PI) was higher ( p < 0.001) of IMF in the breast.…”
Section: Resultsmentioning
confidence: 99%